Ensuring Equal Rights: The Right to Medical Rehabilitation for Victims of Drug Abuse in Parity with Drug Addicts in Legal Proceedings - Ahmad Fauzi; M. Noor Fajar Al Arif F (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2022)
Despite the fact that narcotics are essential for treatment and health care if they are taken improperly or outside the parameters of prescribed therapy, it leads to drug abuse. People who need assistance include drug addicts and those who have been the victims of drug abuse. The rehabilitation procedure, specifically medical and social rehabilitation, is the help in this situation. Drug addicts and victims of drug abuse must be safeguarded. For the treatment and recovery of drug addicts and victims of drug abuse, rehabilitation is preferable to incarceration. Medical rehabilitation can be seen of as an endeavor to treat drug addicts and victims of drug abuse in this case, which is relevant to the issue of medical rehabilitation. This study employs a normative juridical method in the study of law. Primary and secondary data are used, and they are both subjected to quantitative analysis. The study's findings are as follows: Based on the findings of an integrated assessment, legal rehabilitation is carried out. An integral aspect of law enforcement's response to drug misuse crimes is integrated assessment, which advises law enforcement on whether to offer drug addicts recovery programs. Second, rehabilitation efforts are the main focus when dealing with drug addicts, drug abusers, and drug abuse victims. Because this will lead to therapy or activities to be made to remove narcotics, it is necessary to sort out the definitions of drug abusers, addicts, and victims.